Encyclopedia of Governance - Mark Bevir (SAGE Publications, 2007)
The language of governance has spread rapidly in the last thirty years. It describes changes in the nature and role of the state—a shift from bureaucracy to markets and networks. It also denotes a program for global reform—addressingpoverty, gender equality, fair trade, and sustainable environments. Governance provides us with a language to describe and theorize changes in our world. This language has spread across numerous disciplines, including political science, economics, sociology, and public administration. It has also become a topic of concern for political actors: Good governance is among the lending criteria used by the World Bank. Moreover, because governance can refer to the ways political authorities govern alongside associations in civil society, it encourages us to recognize that the activity of governance occurs in schools and colleges, professional organizations, businesses, and the media. The language of governance thus extends to patterns of rule found throughout our daily lives. Businesses and nonprofit organizations are preoccupied with issues of corporate governance, Internet governance, clinical governance, and accountable governance. Governance also provides us with a language to remake our world. Democracy requires us to think about how we are governed in terms of how we govern ourselves. We might ask how to make markets, networks, international organizations, corporations, and other associations democratically accountable. We might also ask what values we want to uphold in our practices of governance. It is important for us to address these questions because, by doing so, we shape the future. We collectively forge new patterns of rule based on new ideas and new values. Although governance has arisen as a ubiquitous language in which to discuss and act in our world, few works translate it into the familiar, commonsense vocabulary of our daily lives. This encyclopedia unpacks the jargon that characterizes much writing in the field to make it more intelligible to researchers, professionals, students, and, I profoundly hope, those citizens who want to pass democratic judgment on the patterns of governance in which they find themselves. Researchers and professionals can refer to it for concise, accurate information on diverse topics. Students will find it offers a clear and accessible introduction and companion to a vast and growing literature. Journalists can refer to it for background information on developments in current affairs. Citizens will find it offers detailed accounts of the ideas and institutions often invoked in political debate. Everyone will gain from it new insights into the global community of which we are all part.